INHERENT GRAVITATIONAL INSTABILITY OF THICKENED CONTINENTAL CRUST WITH REGIONALLY DEVELOPED LOW- TO MEDIUM-PRESSURE GRANULITE FACIES METAMORPHISM - Gerya T.V.; Maresch W.V.; Willner A.P.; Van Reenen D.D.; Smit C.Andre (My University, 2001)
Petrological arguments show that regionally developed low- to medium-pressure, high-temperature granulite facies metamorphism may critically enhance the lowering of crustal density with depth. This leads to gravitational instability of homogeneously thickened continental crust, mainly due to changes in mineral assemblages and the thermal expansion of minerals in conjunction with the exponential lowering of the effective viscosity of rocks with increasing temperature. It is argued that crustal processes of gravitational redistribution (crustal diapirism) contributing to the exhumation of granulite facies rocks may be activated in this way.